Oral intake during labor and its effect on labor progression in Indian women at a tertiary care centre - A., Lekshmi S.; Agarwal, Krishna; Dhiman, Niharika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Assessment of the subjective perception of the women regarding satisfaction of oral intake during labor and the effect of oral intake on cervical dilatation rates and labor duration in low-risk laboring women. Methods: A prospective observational study was conducted from January 2021-July 2022 in a tertiary care hospital with 176 low risk laboring women. Satisfaction of oral intake in labor was assessed by a questionnaire post-delivery and the answers were analysed among various parous groups and were correlated with cervical dilatation rates in active and latent phase and duration of labor. Results: Based on the satisfaction of oral intake in labor, the patients were divided into very satisfied, satisfied, neutral and dissatisfied group. Only 6.7% of primigravidas and 25% of multigravidas were very satisfied with oral intake. Patients who were dissatisfied and not satisfied with oral intake had slower median rates of cervical dilation of 0.45 cm/hour and 1.25 cm/hour in latent and active phase respectively compared to the very satisfied group who had a rate of 0.5 cm/hour and 2.4 cm/hour in the latent and active phase in primigravidas. The mean duration of the first and second stage of labor was 15.5 hours and 50 minutes in the dissatisfied group which was prolonged compared to the patients who had very satisfied oral intake in labor with a duration of 9.6 hours and 30.8 minutes respectively among the primi-gravidas Conclusions: In primi-gravidas the cervical dilation rates were faster in the group who were very satisfied and satisfied with their oral intake compared to the group who were dissatisfied. The labor duration was also prolonged among the dissatisfied group.